2012
DOI: 10.1002/jcc.23047
|View full text |Cite
|
Sign up to set email alerts
|

Interfacing the GROMOS (bio)molecular simulation software to quantum‐chemical program packages

Abstract: The newly implemented quantum-chemical/molecular-mechanical (QM/MM) functionality of the Groningen molecular simulation (GROMOS) software for (bio)molecular simulation is described. The implementation scheme is based on direct coupling of the GROMOS C++ software to executables of the quantum-chemical program packages MNDO and TURBOMOLE, allowing for an independent further development of these packages. The new functions are validated for different test systems using program and model testing techniques. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 48 publications
1
23
0
2
Order By: Relevance
“…76 and the similar TIP3P model while Meier et al . 32 report a much longer D–A distance and smaller bond angle a (OH··O). We confirmed that a steepest-descent geometry optimization starting from the geometry reported by Meier et al .…”
Section: Numerical Accuracy and Performancementioning
confidence: 97%
See 3 more Smart Citations
“…76 and the similar TIP3P model while Meier et al . 32 report a much longer D–A distance and smaller bond angle a (OH··O). We confirmed that a steepest-descent geometry optimization starting from the geometry reported by Meier et al .…”
Section: Numerical Accuracy and Performancementioning
confidence: 97%
“…30 employed density fitting (also called RI- J approximation) for their BP86/TZVP and BLYP/aug-ccpVQZ calculations which slightly affects energetics and geometries while Meier et al . 32 used a simple steepest descent algorithm with the energy as convergence criterium for their geometry optimizations. The latter can be problematic as can be seen from the purely classical SPC results for which we obtain a binding energy and D–A distance in agreement with Jor-gensen et al .…”
Section: Numerical Accuracy and Performancementioning
confidence: 99%
See 2 more Smart Citations
“…GROMOS kann an die ausführbaren Dateien der quantenchemischen Programmpakete MNDO [110] und TURBOMOLE [117] gekoppelt werden. [113] Als Startstrukturen wurden die entsprechenden Kristallstrukturen der Dimere EcCM (PDB-Eintrag 1ECM) [96] und PchB (PDB-Eintrag 3HGX) [97] Die Abstandsanalyse zeigt, dass EcCM und PchB beide nicht in der Lage sind, die "nicht-natürlichen" Substrate, Isochorismat für EcCM (obere zwei Zeilen, vierte Spalte) und Chorismat für PchB (untere zwei Zeilen, erste Spalte) in eine Konformation zu überführen, in der die "nichtnatürliche" Reaktion wahrscheinlicher ist.…”
Section: Molekulares Modell Und Berechnungsverfahrenunclassified